Management of root rot/collar rot of soybean - and B.T. RAUT, S.W. KHODKE* (Indian Phytopathology, 2010)
Root rot and collar rot are the important diseases of soybean, in Vidarbha region of Maharashtra. Seed treatmentand soil application of fungicides, bioagents and its combinations were found effective in increasing seed germination and reducing pre and post emergence mortality. Maximum germination was achieved due to seed treatment with treatment T7 (Thiram + Carbendazim + Trichoderma @ 3+1+4 g/kg) i.e. 89.15, 81.33 and 83.14 per cent in consecutive three years followed by seed treatment with Thiram+Carbendazim 3+1 g/kg (T-6). Minimum pre and post emergence mortality was obtained in T7. Highest pre emergence mortality (15.15%) and post emergence mortality (20.22%) was obtained in control. Grain yield differences were significant, minimum yield was obtained in control i.e. 15.70 q ha-1while highest i.e. 22.50 q ha-1 yield was recorded in T7.